Estimasi Laju Pertumbuhan Penduduk menggunakan Metode Regresi Linier Berganda di Kabupaten Batang - M. Rudi Fanani; Muhammad Yusuf Zain (NUANSA INFORMATIKA, 2024)
Population growth in an area is very important for development and as a benchmark for development and progress. One way to estimate/estimate population growth is to use Data Mining techniques. Data mining is able to analyze data into information. This research will discuss the population growth of Batang Regency, Central Java in 2024. The estimation technique that will be used is Multiple Linear Regression. This method was chosen because it can make estimates/predictions by utilizing past data regarding population growth so that it can produce a relationship pattern. This Multiple Linear Regression method aims to produce the best predictions. The research data used is population data in Batang Regency in 2019-2023. Based on research that has been carried out, the results show a population growth of 853,800 people in 2024. This figure shows a population increase of 24,917 people compared to 2023 of 828,883 people with an increase percentage of 3%. The benefits of this research can be conveyed to the Batang Regency Government as material for decision and policy making in the year.